Single-port retroperitoneal renal biopsy using standard urological instruments - Guerra, Rodrigo [UNESP]; Ordones, Flávio Vasconcelos [UNESP]; Yamamoto, Hamilto Akihissa [UNESP]; Kawano, Paulo Roberto [UNESP]; Amaro, Joao Luiz [UNESP] (Brazilian Soc Urol, 2015)
Objective: To describe the surgical technique and initial experience with a single-port retroperitoneal renal biopsy (SPRRB).Materials and Methods: Between January and April 2013, five children underwent SPRRB in our hospital. A single 1.5 cm incision was performed under the 12th rib at mid-axillary line, and an 11 mm trocar was inserted. A nephroscope was used to identify the kidney and dissect the perirenal fat. After lower pole exposure, a laparoscopic biopsy forceps was introduced through the nephroscope working channel to collect a renal tissue sample.Results: SPRRB was successfully performed in five children. The mean operative time was 32 minutes, and mean estimated blood loss was less than 10 mL. The hospital stay of all patients was two days because they were discharged in the second postoperative day, after remaining at strict bed rest for 24 hours after the procedure. The average number of glomeruli present in the specimen was 31.Conclusion: SPRRB is a simple, safe and reliable alternative to open and videolaparoscopic approaches to surgical renal biopsy.
Keywords: Kidney; Biopsy; Retroperitoneal Space; Surgical Procedures, Operative; Minimally Invasive Surgical Procedures; Laparoscopy